A mechanistic multi-centre, parallel group, randomised placebo controlled trial of Mesalazine for treatment of irritable bowel syndrome with diarrhoea (IBS-D) - Lam, Ching; Tan, Wei; Leighton, Matthew; Hastings, Margaret; Lingaya, Melanie; Falcone, Yirga; Zhou, Xiaoying; Xu, Luting; Whorwell, Peter; Walls, Andrew; Zaitoun, Abed M.; Montgomery, Alan; et al. (BMJ Publishing Group, 2015)
Introduction: Immune activation has been reported in the mucosa of irritable bowel syndrome patients with diarrhoea (IBS-D) and some small studies have suggested that Mesalazine may reduce symptoms. We performed a double blind, randomised placebo controlled trial of 2g Mesalazine twice daily versus placebo for 3 months in Rome III criteria IBS-D patients. Primary outcome was daily average stool frequency during weeks 11-12; secondary outcomes were abdominal pain, stool consistency, urgency and satisfactory relief of IBS symptoms. Methods: Participants were randomised after a 2-week baseline stool diary. All participants completed a 12-week stool diary and at the end of each week recorded the presence of “satisfactory relief of IBS symptoms”. Results: 136 patients with IBS-D (82 F, 54 M) were randomised, 10 patients withdrew from each group. Analysis by intention to treat showed the daily average stool frequency during weeks 11 and 12 were mean (SD), 2.8 (1.2) in Mesalazine and 2.7 (1.9) in placebo group with no significant group difference (95% confidence interval) 0.1 (-0.33,0.53); p=0.66. Mesalazine did not improve abdominal pain, stool consistency nor percentage with satisfactory relief compared to placebo during the last 2 weeks follow up. Conclusion: This study does not support any clinically meaningful benefit or harm of Mesalazine compared with placebo in unselected IBS with diarrhoea. More precise subtyping based on underlying disease mechanisms is needed to allow more effective targeting of treatment in IBS. (ClinicalTrials.gov number NCT01316718)